Characteristics of asthmatic patients with and without repeat emergency department visits at an inner city hospital. (August 2014) - Pai, Sucheta; Mancuso, Carol A.; Loganathan, Raghu; Boutin-Foster, Carla; Basir, Riyad; Kanna, Balavenkatesh
Abstract Objective: The objective of this study was to document the frequency and clinical characteristics associated with repeat emergency department (ED) visits for asthma in an inner city population with a high burden of asthma. Methods: During an ED visit for asthma in an inner city hospital ('index visit'), patients completed a valid survey addressing disease and behavioral factors. Hospital records were reviewed for information about ED visits and hospitalizations for asthma during the 12 months before and the 90 days after the index visit. Results: One hundred and ninety-two patients were enrolled; the mean age was 42 years, 69% were women, 36% were black, 54% were Latino, 69% had Medicaid, and 17% were uninsured. 100 patients (52%) were treated and released from the ED, 88 patients (46%) were hospitalized, and 4 patients (2%) left against medical advice. During the subsequent 90 days, 64 patients (33%) had at least one repeat ED visit for asthma and 27 (14%) were hospitalized for asthma. In a multivariate model, more past ED visits (OR 1.7, 95% CI 1.4, 2.1; p < 0.0001) and male gender (OR 2.5, 95% CI 1.2, 5.4; p = 0.02) remained associated with having a repeat ED visit. Most patients had the first repeat ED visit within 30 days and 18 returned within only 7 days. Among all patients with a repeat visit, those who were not hospitalized for the index visit were more likely to have a repeat visit within 7 days (37%) compared to those who were hospitalized (17%) (p = 0.05 in multivariate analysis). Conclusions: Repeat ED visits were prevalent among inner city asthma patients and most occurred shortly after the index visit. The strongest predictors of repeat visits were male gender and more ED visits in the 12 months before the index visit.